2022
DOI: 10.3389/fspas.2022.850409
|View full text |Cite
|
Sign up to set email alerts
|

Parameterizing the AGN Radius–Luminosity Relation from the Eigenvector 1 Viewpoint

Abstract: The study of the broad-line region (BLR) using reverberation mapping has allowed us to establish an empirical relation between the size of this line-emitting region and the continuum luminosity that drives the line emission (i.e., the RHβ − L5100 relation). To realize its full potential, the intrinsic scatter in the RHβ − L5100 relation needs to be understood better. The mass accretion rate (or equivalently the Eddington ratio) plays a key role in addressing this problem. On the other hand, the Eigenvector 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 104 publications
2
18
0
Order By: Relevance
“…The constraints on the intercept parameter of the C 𝑅 − 𝐿 relation, 𝛽 , range from a low of 0.970 +0.136 −0.108 (flat XCDM) to a high of 1.076 +0.087 −0.074 (non-flat 𝜙CDM), with a difference of 0.68𝜎. A summary value of the measured C 𝑅 − 𝐿 relation slope, 𝛾 0.45 ± 0.04, indicates that it is about 1𝜎 lower than and consistent with the prediction of simple photoionization theory (𝛾 = 0.5, Karas et al 2021;Panda 2022), on the other hand a summary value of the measured Mg 𝑅 − 𝐿 relation slope, 𝛾 0.3 ± 0.05 (also see Khadka et al 2021aKhadka et al , 2022a, indicates that it is about 4𝜎 lower than 𝛾 = 0.5. 6 Khadka et al (2021a6 Khadka et al ( , 2022a had earlier shown that the symmetric errors Mg cosmological constraints are mutually consistent with those from 𝐻 (𝑧) + BAO data.…”
Section: Constraints From C Mg and C + Mg Qso Datasupporting
confidence: 52%
See 1 more Smart Citation
“…The constraints on the intercept parameter of the C 𝑅 − 𝐿 relation, 𝛽 , range from a low of 0.970 +0.136 −0.108 (flat XCDM) to a high of 1.076 +0.087 −0.074 (non-flat 𝜙CDM), with a difference of 0.68𝜎. A summary value of the measured C 𝑅 − 𝐿 relation slope, 𝛾 0.45 ± 0.04, indicates that it is about 1𝜎 lower than and consistent with the prediction of simple photoionization theory (𝛾 = 0.5, Karas et al 2021;Panda 2022), on the other hand a summary value of the measured Mg 𝑅 − 𝐿 relation slope, 𝛾 0.3 ± 0.05 (also see Khadka et al 2021aKhadka et al , 2022a, indicates that it is about 4𝜎 lower than 𝛾 = 0.5. 6 Khadka et al (2021a6 Khadka et al ( , 2022a had earlier shown that the symmetric errors Mg cosmological constraints are mutually consistent with those from 𝐻 (𝑧) + BAO data.…”
Section: Constraints From C Mg and C + Mg Qso Datasupporting
confidence: 52%
“…However, we find a 2.3𝜎 difference in the measured slopes of the C and Mg 𝑅 − 𝐿 relations, in the flat ΛCDM model asymmetric error bars results of Table 3, or from the summary values of the measured C and Mg 𝑅 − 𝐿 relation slopes, 𝛾 0.45 ± 0.04 and 𝛾 0.3 ± 0.05. And while the C slope is only about 1𝜎 lower than the 𝛾 = 0.5 slope predicted by simple photoionization theory (Bentz et al 2013;Karas et al 2021;Panda 2022) or a dust-based model of the BLR (Czerny & Hryniewicz 2011), the Mg slope is about 4𝜎 lower than 𝛾 = 0.5, which is more statistically significant.…”
Section: Discussionmentioning
confidence: 73%
“…(vi) The smaller slope of the Mg -based 𝑅 − 𝐿 relation in comparison with both the H𝛽-based 𝑅 − 𝐿 correlation slope (Martínez-Aldama et al 2019;Khadka et al 2021a) and the slope predicted by simple photoionization theory (𝛾 ion =0.5; Karas et al 2021;Panda 2022) is either caused by the source selection effect (cumulation of SDSS-RM sources at intermediate luminosities) or by the different photoionization mechanism and/or distribution of Mg -emitting gas (e.g. lack of the intrinsic "breathing" effect for Mg -emitting material; Guo et al 2020;Wang et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…This is unlike H𝛽 sources where high-accretors exhibit a larger scatter with respect to low-R Fe sources. (Martínez-Aldama et al 2019;Du & Wang 2019;Khadka et al 2021a;Panda 2022), (ii) The sample of 66 Mg quasars used here is about a factor of 2 smaller than the H𝛽 sample of 118 sources. The majority of the Mg sources, 57, are from the SDSS-reverberation-mapping (SDSS-RM) program (Homayouni et al 2020) and cover a rather narrow range in monochromatic luminosity and rest-frame timedelay.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 2, we show the distributions of FWHM Hβ , σ Hβ , and the broad Hβ shape D Hβ,mean ≡ FWHM Hβ /σ Hβ from the mean spectrum for the RM subsample (red lines). It was found that D Hβ,mean has a relation with L Bol /L Edd or M  (e.g., Du et al 2016a;Yu et al 2020a;Panda 2022). We also show the distribution of FWHM Hβ and σ Hβ from the single-epoch spectrum for the SDSS subsample (blue lines).…”
Section: Samples and Data Analysismentioning
confidence: 87%